DETERMINANT YIELD GOVERNMENT BOND TRADED FROM 2016 TO 2021 - Mia Agusty, Rosana; Santoso Marsoem, Bambang (Dinasti Publisher, 2021)
A Government Bond is a significant financial instrument for the state budget of Indonesia Government. It has become important and quite attractive among other financial instruments. Using BI 7-Day Repo Rate, Inflation, Money Supply, Indonesia Composite Index, and USD/IDR Exchange Rate as independent variables, this research has been done to determine Government Bond Yield. The research population is bond issued by Indonesia Government. The sampling is 10-years traded Government Bond fixed rate serries during 2016-2021 with 300 data collected which since 2020 Indonesia has been facing the Covid-19 pandemic that affected the global economy and financial markets. This research finds that Government Bond Yield positively affected by BI 7-Day Repo Rate, Inflation Rate, and USD/IDR Exchange Rate, while negatively affected by Money Supply, yet Indonesia Composite Index and Covid-19 pandemic has no effect on the Government Bond Yield.